Innovative green-technology SMEs as an opportunity to promote financial de-risking - Elena Verdolini; Céline Bak; Joël Ruet; Anbumozhi Venkatachalam (Economics: The Open-Access, Open-Assessment E-Journal, 2018)
The authors recommend that the G20 target innovative green-technology SMEs as an opportunity to promote financial de-risking while addressing Paris Agreement commitments and UN Sustainable Development Goals. This should be achieved by creating signals for private investors through: (1) a reporting system that can help monitor the scale-up of green-technology SMEs; (2) the use of public funds to signal innovative green-technology SMEs to investors; and (3) the inclusion of SMEs in the design of green finance platforms. By implementing these recommendations, the G20 will ensure that innovative, low-carbon SMEs become attractive, low(er)-risk investment opportunities for the private sector.
Keywords: O31; Q55; Q58; E60; 330; Innovation; green technology; eco-efficiency; SMEs; financial de-risking